2023
DOI: 10.3389/fnagi.2023.1107320
|View full text |Cite
|
Sign up to set email alerts
|

Altered topological properties of functional brain networks in patients with first episode, late-life depression before and after antidepressant treatment

Abstract: ObjectivesTo preliminarily explore the functional activity and information integration of the brains under resting state based on graph theory in patients with first-episode, late-life depression (LLD) before and after antidepressant treatment.MethodsA total of 50 patients with first-episode LLD and 40 non-depressed controls (NCs) were recruited for the present research. Participants underwent the RBANS test, the 17-item Hamilton depression rating scale (HAMD-17) test, and resting-state functional MRI scans (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…In this study, after a 6-month of antidepressant treatment, the results of the TMT and Stroop task test indicated no statistically significant difference between the LLD baseline group and the LLD follow-up group. This finding aligned with our previous study, 34 which demonstrated that the LLD follow-up group exhibited enhanced performance in immediate memory, delayed memory, and speech function compared to the LLD baseline group. However, there was no significant alteration observed in visual space and attention ability.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, after a 6-month of antidepressant treatment, the results of the TMT and Stroop task test indicated no statistically significant difference between the LLD baseline group and the LLD follow-up group. This finding aligned with our previous study, 34 which demonstrated that the LLD follow-up group exhibited enhanced performance in immediate memory, delayed memory, and speech function compared to the LLD baseline group. However, there was no significant alteration observed in visual space and attention ability.…”
Section: Discussionsupporting
confidence: 92%
“…After 6 months of SSRIs treatment, compared with the LLD baseline group, the congruency between word color and word meaning led to enhanced activation of the left middle cingulate gyrus in the LLD follow‐up group. Similarly, we recently found that after 6 months of SSRIs treatment, patients in the LLD follow‐up group had an increased degree centrality (DC) value in the left median cingulate and paracingulate gyrus compared to the LLD baseline group 34 . In graph theory, DC refers to the degree of each node in the network in the node attribute index, and the higher the value, the more likely the node is to become a hub in the network, the higher the value, the more likely the node is to become a hub in the network 44 .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations